Study the Lipoxygenase Enzyme Activity on Patients With Thalassemia in Kirkuk Governorate - Wisam Sbhan Khalf Mohamed Aljumaily; Khalaf Naeef Mohamed (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study was conducted at the Thalassemia Center of Azadi Educational Hospital, Kirkuk Health Directorate, Iraq, from June 1, 2024, to October 1, 2024. The study sample included 75 individuals, both males and females, aged between 4 and 67 years, divided into two groups: the first group comprised 50 thalassemia patients, while the control group included 25 healthy individuals. The results indicated a significant effect of thalassemia on the studied variables, as the disease led to increased levels of white blood cells, erythrocyte sedimentation rate, total iron-binding capacity, malondialdehyde, iron concentration, and lipoxygenase enzyme, recording values of 10.9 × 103 cells/mL, 25.36%, 321.84 µg/dL, 721.12 mmol/L, 2788.9 ng/dL, and 226.2 IU/L, respectively. In contrast, thalassemia reduced hemoglobin levels to 8.57 g/L. The gender category significantly affected both malondialdehyde and iron concentrations, while the age category significantly impacted white blood cell levels, total iron-binding capacity, serum iron, and lipoxygenase enzyme. Among the interactions, the most influential factor was found in the group of female patients over 30 years old, who recorded the highest significant concentrations of white blood cells and malondialdehyde, reaching 12.26 × 103 cells/mL and 1090 mmol/L. Conversely, female patients under 15 years showed the highest significant averages for the percentage of erythrocyte sedimentation rate and iron concentration, at 28% and 3270 ng/dL, respectively. Meanwhile, female patients aged 15-30 years exhibited the highest significant concentrations for total iron-binding capacity and lipoxygenase enzyme, at 361.8 µg/dL and 234 IU/L, respectively. Male patients aged 15-30 years recorded the lowest significant hemoglobin concentration, which was 7.33 g/L.